Understanding public preferences for learning about uncertain science: measurement and individual difference correlates - Ratcliff, Chelsea L.; Harvill, Blue; Wicke, Rebekah (Frontiers in Communication, 2023)
Although uncertainty is inherent in science, public audiences vary in their openness to information about preliminary discoveries and the caveats and limitations of research. These preferences shape responses to science communication, and science communicators often adapt messaging based on assumed preferences. However, there has not been a validated instrument for examining these preferences. Here, we present an instrument to capture preferences for information about uncertainty in science, validated with a large U.S. adult sample. Factor analysis results show that preferring certain scientific information and preferring uncertain scientific information are orthogonal constructs requiring separate measures. The final Preference for Information about Uncertain Science (or “PIUS-11”) scale comprises two dimensions: preferring complete information (i.e., caveats, limitations, and hedging included) and being open to learning about preliminary science. The final Preference for Certain Science Information (or “PCSI-9”) scale comprises two dimensions: preferring streamlined information (i.e., caveats, limitations, and hedging removed) and preferring to learn only about established science. We present psychometric properties of each scale and report observed relationships between each set of preferences and an individual’s scientific understanding, trust in science, need for cognitive closure, and sociodemographic factors.